Implementation of Micro Teaching in Developing Basic Teaching Skills of Prospective Islamic Religious Education Teacher Students - Wantika Wantika (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
This research is motivated by the dynamics of Islamic education in the 21st century, which faces complex challenges, ranging from the dominance of Western educational paradigms to the digital identity crisis among young Muslims. This phenomenon demands the strengthening of Islamic epistemology that integrates aspects of the spirituality of revelation with the rationality of modern science through the professional competence of educators capable of stimulating students' critical thinking abilities. This study aims to comprehensively evaluate the effectiveness of the microteaching course in honing basic teaching skills in students of the Islamic Religious Education (PAI) Study Program. The research method used is descriptive qualitative with systematic observation techniques of eight basic teaching skills in the microteaching laboratory. The results showed a significant increase in the ability to open lessons (88%) and the skill of providing reinforcement (82%). However, significant challenges were found in interactive classroom management (79%) and limitations in the use of innovative media due to the lack of supporting facilities such as projectors. In conclusion, it is necessary to revitalize the microteaching method with a greater emphasis on the use of creative media, digital literacy, and conflict management simulations to develop the professional readiness of prospective PAI teachers who are competent and solution-oriented before entering the real school environment.